A profile of biotechnology and information technology venture firms in Japan: firm-level and managerial characteristics. (1st January 2003) - Lynskey, Michael J.
High-technology venture firms are considered to play an important role in the knowledge-based economy. In Japan, policy makers have belatedly advocated the creation of such firms, focusing on two primary fields - biotechnology and information technology (IT) - which are expected to make major economic contributions to Japan's international competitiveness, to the creation of new industries and to employment opportunities. Although a number of empirical studies have been conducted into such high-technology venture firms in the West, very few, if any, comparable studies have been undertaken in Japan using data from indigenous firms. This paper addresses this gap by using firm-level data from an original questionnaire survey. Our purpose is to profile several firm-level and managerial characteristics of biotechnology and IT venture firms in Japan to understand how they differ, if at all, from those in the West.